Penjatuhan Sanksi Terhadap Pelaku Tindak Pidana Pencucian Uang Dalam Perspektif Tujuan Hukum - Kelian, Jubeda; Leasa, Elias Zadrach (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Money laundering is a serious crime that has a significant impact on the stability of the national economy and financial system. The complexity of money laundering schemes requires the application of a system of evidence and the imposition of criminal sanctions that are consistent with the objectives of the law, namely justice, legal certainty, and public interest.Purposes of the Research This study aims to analyze and discuss the burden of proof in money laundering cases, as well as to analyze and discuss the imposition of sanctions on perpetrators of money laundering from the perspective of the objectives of the law.Methods of the Research: This study is a normative legal research study that employs a statutory approach, a conceptual approach, and a case-based approach. The legal materials used include primary legal sources and secondary legal sources. The legal materials were collected through a literature review. The processing of the legal materials involved the following stages: identification of legal issues, searching for primary and secondary legal materials, and grouping of relevant legal materials. All legal materials obtained were subsequently analyzed qualitatively.Results / Findings / Novelty of the Research: The results of this study indicate that the imposition of criminal sanctions on money laundering offenders aligns with the legal objectives of legal certainty through clear criminalization, separation from the predicate offense, and anti-tipping-off measures. The Justice Perspective, where criminal sanctions aim to restore a sense of justice in society, ensuring that proceeds of crime are not enjoyed by the perpetrators, through asset forfeiture, punishing both active and passive perpetrators, and creating a deterrent effect. The Utility Perspective, which involves protecting the financial system, recovering state losses, and preventing further criminal acts.